Patent law and innovations of the Polish economy : Analysis of the current situation and recommendations for the future - Karpińska, Kinga; Protasiewicz, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
One of the key elements of modern economies is their innovation, measured in many ways. The measures of innovation most often include R&D expenditure (expenditure side) and patents (effects side). Undoubtedly, the level of expenditure on research activities is important, but the true picture of an innovative economy is provided by the side of the achieved results, i.e. patents. The purpose of the article is to analyze the impact of patent law (organizational, financial, and legal conditions, and thus the number of filed and patented solutions) on the level of innovativeness on the example of the Polish economy. The analysis was based on a review of domestic and foreign literature and legal acts on patent protection at the national, regional (European) and international levels on the one hand, and innovation in Poland and European countries on the other. To assess the level of innovativeness data from the Global Innovation Index, the Central Statistical Office (GUS) and the European Innovation Scoreboard were used. Comparison of these data made it possible to articulate several conclusions. First, patent law is considered too complex and unclear for research applicants. Moreover, the awareness of patent applicants in Poland is still quite low, especially if the entity is a small enterprise. An undoubted barriers to the patent activity are also the costs that must be borne during the entire patent procedure and the waiting time for the procedure to be completed. Future research should focus on surveying businesses in Poland about their views on patent law and possible changes to improve its operation, allowing for a more detailed analysis of the issue.
Keywords: innovation; patent law; patents; Polish economy